Endoscopic Surgery for Facial Lipoma Excision. Issue 3 (2001) - Koike, H.; Kitano, H.; Fujimura, M.; Kinoshita, T.; Kataoka, H.; Hirano, M.; Seno, S.; Kitajima, K.
Abstract : Minimally invasive endoscopic surgery in the neck, first reported by Gagner in 1996, has been adopted by a number of other surgical specialties. We have developed new techniques for performing endoscopic enucleation lipoma. Using our new techniques, various complications, such as injury to nerves and vessels, are prevented. The technique generates cosmetically satisfying results. Expansion of minimally invasive surgery into the facial area will be enhanced by the future development of instruments for this area, and decrease operating time and hospital stay.